PROSES BERPIKIR SISWA TUNA GRAHITA SEDANG DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA BERDASARKAN TAHAPAN PIAGET DI SMPLB-C TPA BALUNG - Lestari, Harin Tripuji; Susanto, Susanto; Fatahillah, Arif (Department of Mathematics Education , University of Jember, 2017)
Abstract. The purpose of this research is to describe seventh grade medium mental retardation students' thinking process in solving mathematics problem of addition and subtraction of algebraic form similar rate. The type of research was a descriptive study with qualitative approach. Instruments that were used in this research are contextual mathematical problem, interview guidelines, and validation sheet. The coeficient of validation instrument test is 4,59 and the coeficient of validation instrument interview guidelines is 4,40. Methods of data collection in this research are test and interview. The reseach subject is two medium mental retardation students' in SMPLB-C TPA Balung. Thinking process were analyzed in this reseach based on thinking process indicator in Piaget's step. Based of this research was subjects had difficulty in understanding, remembering, and solving the problem. This is because the level of medium mental retardation intelligence to low i.e. between 40-54, so the subject had disequilibrium, assimilation or accommodation, equilibrium, and back to disequilibrium. Keywords: Piaget's thinking process, medium mental retardation, addition and subtraction of algebraic form similar rate problem.